Integrated marketing communications - Kitchen, Philip J. (Henry Stewart Talks, 2012)
IMC Defined, Structural characteristics, Rapidity of change, An end of mass marketing, The paradox, What should be integrated?, To deliver what benefits?, The 'seeming issues', Progressive issues in relation to brands and branding, An ad agency example, The commitment to integration, Is IMC 'integrated'?, The importance of IMC, Campaign (1997 & 1998) the importance of IMC, Paradigm shift in how marcoms works, CAB hierarchy of effects, The importance of IMC, Expanding brand integration: broadening influences, Branding & integration, Real integration, The lead discipline driven by client-set marketing objectives